Default mode network and extrastriate visual resting state network in patients with Parkinson's disease dementia - Rektorova, I; Krajcovicova, L; Marecek, R; Mikl, M (Neuro-degenerative diseases, 2012)
AIMS: Using fMRI, we evaluated the default mode network (DMN) and the extrastriate visual resting state network (ESV-RSN) in 14 patients with Parkinson's disease dementia (PDD) as compared with 18 patients with Parkinson's disease (PD) without dementia and 18 healthy controls (HC). METHODS: We analyzed the seed-based functional connectivity of both resting state data and deactivations during a visual complex scene-encoding task. RESULTS: Using the posterior cingulate cortex/precuneus as a seed for the DMN analysis, we observed significant decreases of connectivity in the right inferior frontal gyrus in PDD as compared to PD and HC. Using the caudate nucleus as a seed for the ESV-RSN analysis, we found significant decreases of connectivity in the left and right inferior occipital gyrus in PDD as compared to HC. CONCLUSION: Differences in functional connectivity patterns between PDD and PD/HC were observed in areas known to be engaged in stimulus-driven reorienting of attention and in visual processing.
Keywords: mapování mozku; Male; Dementia; Oxygen; Photic Stimulation; magnetická rezonanční tomografie; demence; týlní lalok; statistika jako téma; zrakové dráhy; Adult; rozpoznávání (psychologie); Aged; dospělí; Image Processing, Computer-Assisted; mužské pohlaví; senioři; Rest; odpočinek; Neuropsychological Tests; Occipital Lobe; senioři nad 80 let; počítačové zpracování obrazu; Brain Mapping; lidé; kyslík; ženské pohlaví; Humans; Visual Pathways; Aged, 80 and over; neuropsychologické testy; Recognition, Psychology; Magnetic Resonance Imaging; Female; Parkinson Disease; Parkinsonova nemoc; Statistics as Topic; lidé středního věku; světelná stimulace; Middle Aged